A Temporal Map of Coaching - Theeboom, Tim; Van Vianen, Annelies E. M.; Beersma, Bianca (Frontiers in Psychology, 2017)
Economic pressures on companies, technological developments, and less stable career paths pose potential threats to the well-being of employees (e.g. stress, burn-out) and require constant adaptation. In the light of these challenges, it is not surprising that employees often seek the support of a coach. The role of a coach is to foster change by facilitating a coachees' movement through a self-regulatory cycle with the ultimate aim of stimulating sustained well-being and functioning. While meta-analytic research indicates that coaching interventions can be effectively applied to assist employees in dealing with change, the current literature on coaching lacks solid theoretical frameworks that are needed to build a cumulative knowledge-base and to inspire evidence-based practice. In this conceptual analysis, we examine the coaching process through a temporal lens. By doing so, we provide an integrated theoretical framework: a temporal map of coaching. In this framework, we link seminal concepts in psychology to the coaching process, and describe which competencies of coachees are crucial in the different stages of change that coaching aims to bring about. During the preparatory contemplation stage, targeting coachees’ awareness by enhancing their mindfulness and environmental receptiveness is important. During the contemplation stage, coachees’ willingness and perceived ability to change are central competencies. We propose that coaches should therefore foster intrinsic goal orientation and self-efficacy during this stage. During the planning stage, coaches should focus on goal-setting and implementation intentions. Finally, during the maintenance/termination stage, stimulating coachees' reflection is especially important in order to help them to integrate their learning experiences. The framework delineated in this paper contributes to the understanding of coaching as a tool to assist employees in dealing with the challenges of an increasingly dynamic work-environment and yields concrete suggestions for future theory development and research on coaching.